1995
DOI: 10.1002/jcb.240590412
|View full text |Cite
|
Sign up to set email alerts
|

Human myeloid cell nuclear differentiation antigen binds specifically to nucleolin

Abstract: The human myeloid cell nuclear differentiation antigen (MNDA) is a nuclear protein expressed specifically in cells of the myelomonocytic lineage and regulated by interferon alpha in a cell-specific fashion. MNDA is also a member of a family of interferon-regulated genes of unknown function. In an effort to elucidate the function of MNDA, three techniques (affinity purification, coimmunoprecipitation, and protein blot assay) were used to characterize its specific protein binding activities. Microsequence analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Early studies into the role of MNDA suggested an involvement in myeloid differentiation. This idea was supported by studies revealing that MNDA can bind nucleolin and nucleophosmin [14,15], both of which have been shown to be involved in the maturation and biosynthesis of ribosomes. The noted nuclear localisation, and lineage-and stage-specific expression of MNDA suggested that this PYHIN protein may play a role in regulating gene transcription.…”
Section: Early Research On the Human Pyhinsmentioning
confidence: 89%
“…Early studies into the role of MNDA suggested an involvement in myeloid differentiation. This idea was supported by studies revealing that MNDA can bind nucleolin and nucleophosmin [14,15], both of which have been shown to be involved in the maturation and biosynthesis of ribosomes. The noted nuclear localisation, and lineage-and stage-specific expression of MNDA suggested that this PYHIN protein may play a role in regulating gene transcription.…”
Section: Early Research On the Human Pyhinsmentioning
confidence: 89%
“…Recombinant MNDA was prepared using the pQE30 expression system as described previously [24]. To promote 125 I-labeling primarily in the His-tag region, the purified rMNDA was first dialyzed at 4°C with three changes against 20 mM Tris-HCl pH 8.2, 500 mM NaCl, 10% glycerol, 0.1% NP-40, 1 mM PMSF to remove imidazole.…”
Section: Labeling Of Mndamentioning
confidence: 99%
“…The pQE30-MNDA, described previously [24], was used to prepare His-tagged recombinant MNDA. C-terminal deletion mutations were prepared from the pQE30-MNDA construct using the Erase-a Base System (Promega).…”
Section: Generation Of Mnda Deletion Mutantsmentioning
confidence: 99%
See 2 more Smart Citations